Preparation of Engineered Extracellular Vesicles Derived from Human Umbilical Cord Mesenchymal Stem Cells with Ultrasonication for Skin Rejuvenation - Wang, Lixue (ACS Omega, 2019)
[Image: see text] Extracellular vesicles (EVs) are lipid-bilayer-enclosed vesicles of submicron size that are secreted by various cells. As mediators of intercellular communication, EVs can alter the physiological state of recipient cells by delivering encapsulated proteins and nucleic acids. Incontestably, growing evidence has shown important biological roles and the clinical relevance of EVs. The use of stem cell-derived EVs as a cell-free therapeutic modality for skin treatment has emerged as a promising application in dermatology. However, the moderate isolation efficiency of prevalent ultracentrifugation and low secretion rate make the massive low-cost production of EVs difficult. Here, we report development of engineered EVs (eEV) derived from human umbilical cord mesenchymal stem cells (hucMSCs) for skin treatment. Ultrasonication was used to shear intact hucMSCs for only 1 min, followed by regular centrifugation and filtration for producing nanoscale eEVs. This approach has ∼20-fold higher yield and ∼100-fold faster production than that of naturally secreted EVs (nsEV), while the production cost decreased to less than 10%. The eEVs have similar morphology, size distribution, and typical protein markers compared to nsEVs. Moreover, in vitro, both nsEVs and eEVs promote the proliferation and migration of dermal fibroblasts and increase in the expression of collagen, elastin, and fibronectin, whereas the matrix metalloproteinases-1 (MMP-1) and MMP-3 production can be significantly reduced. The wound-healing study in mice showed that both nsEVs and eEVs promote wound recovery in comparison with the controls. In sum, our results indicate that hucMSC-derived eEVs prepared by ultrasonication potentially can be used to increase skin extracellular matrix and enhance skin rejuvenation.